The Cost of Regulatory Compliance in the United States - Francesco Trebbi; Miao Ben Zhang; Michael Simkovic (Center for Economic Studies and ifo Institute (CESifo), 2023)
One of the key questions in the study of regulation is whether the costs of regulatory compliance fall homogeneously on all businesses or whether certain firms, for instance small ones, are especially penalized. We quantify firms' compliance costs in terms of their labor spending to adhere to government rules. Using comprehensive establishment-level occupational microdata and occupation-specific task information, we recover the proportion of a firm's wage bill attributable to employees engaged in regulatory compliance. On average for 2002-14, regulatory costs account for 1.34% to 3.33% of a firm's wage bill, totaling up in 2014 to 239 billion, and to 289 billion when adding capital equipment costs. Our findings reveal an inverted-U relation between firms' regulatory compliance costs and their scale of employment, indicating that firms with approximately 500 employees face compliance costs that are about 40 percent higher as a share of total wages compared to small or large firms. Finally, we develop an instrumental variable methodology to disentangle the influence of regulatory requirements and enforcement in driving firms' compliance costs.
Keywords: P00; 330; regulation; compliance costs; labor task; occupation; firm growth; economies of scale; regulatory requirement; enforcement